New diprenylated dihyrochalcones from leaves of Artocarpus elasticus - Ramli, Faiqah; Rahmani, Mawardi; Kassim, Nur Kartinee; Mohd Hashim, Najihah; Md. Sukari, Mohd. Aspollah; Md. Akim, Abdah; Go, Rusea (Elsevier, 2013)
Two new diprenylated dihydrochalcones, elastichalcone A 1 and elastichalcone B 2 and three known compounds were isolated from the leaves of Artocarpus elasticus. Their structures were determined by various spectroscopic techniques (UV, IR, MS, 1D-NMR and 2D-NMR). Elastichalcone B 2 and a known compound exhibited good free radical scavenging activity with IC50 values of 11.30 and 11.89 μg/ml, respectively. © 2013 Phytochemical Society of Europe.